A construção histórica do negro como alvo do encarceramento em massa no Brasil / The Historical Construction of the Black People as a Target of Mass Incarceration in Brazil - Santos, Renan Daniel Trindade dos; Gomes, Marcus Alan Melo (REVISTA QUAESTIO IURIS, 2022)
Resumo O Brasil vivenciou um dos mais duradouros processos de escravização, se estendendo do século XVI ao final do século XIX, quando houve a abolição formal da escravidão. Diante da ruptura abrupta, não é difícil concluir que muitos setores da sociedade brasileira herdaram a mentalidade escravocrata moldada e difundida em séculos de formação social e econômica do país. O sistema penal não escapou a esse fenômeno, aqui analisado a partir do cárcere e sua relação com a senzala. Mais tarde a punição foi monopolizada pelo Estado, criminalizando negros libertos e escravizados pela prática de mendicância, vadiagem, capoeira. Contemporaneamente esta herança se reflete na população carcerária brasileira, da qual 66,7% são de origem negra. A partir disso, este artigo debate o problema: É possível apontar uma construção histórica do negro no sistema penal brasileiro? O marco teórico da pesquisa se concentra no pensamento de Karl Marx, Octavio Ianni, Lilian Schwarcz, Jessé Souza, E. Raul Zaffaroni, Ana Flauzina para apontar a seletividade histórica e racializada do sistema penal brasileiro. O artigo se desenvolve a partir de pesquisa bibliográfica e documental, mediante exame dos dados reunidos no Anuário Brasileiro de Segurança Pública de 2020, que indica o aumento da população carcerária negra no país. Palavras-chaves: escravidão; punição; negros; encarceramento; sistema penal. Abstract Brazil experienced one of the most enduring historical processes of enslavement of blacks, which extended from the 16th century to the end of the 19th century, when there was the formal abolition of slavery. In the face of the abrupt rupture, it is not difficult to conclude that many sectors of Brazilian society have inherited the mentality of slavery, after all it has been almost four centuries of social and economic formation from the enslavement of black people. The penal system, analyzed here from prison, previously represented by the slave quarters where blacks were punished by their lords, has not escaped this phenomenon. Later that punishment passed was monopolized by the State, criminalizing freed blacks and still slaves for the practice of begging, vagrancy, capoeira. Nowadays this slavery heritage is reflected in the Brazilian prison population, of which 66.7% are of black origin. Based on these findings, this article discusses the problem: Is it possible to point to a historical construction of blacks in the Brazilian penal system? Marx, Ianni, Schwarcz, Souza, Zaffaroni, Flauzina, among others, were used as a theoretical framework to point out the historical and racialized selectivity of the Brazilian penal system. Therefore, the research took a bibliographic form, especially from the Brazilian Yearbook of Public Security of 2020, which points out the population growth of black people in the country. Keywords: slavery; punishment; blacks; incarceration; penal system.